Amazing creatures. - Huggins-Cooper, Lynn. (Laguna Hills, CA : QEB pub, 2008)
"Describes unusual species of mammals, reptiles, and fish that have unique features and behaviors that help them adapt to their habitats"--Provided by publisher.
Includes index.
Keywords: Animals --Miscellanea --Juvenile literature; Physiology --Miscellanea --Juvenile literature